Investigation of doping techniques on the silicon based capacitor / Ahmad Sabirin Zoolfakar ...[et al.] - Zoolfakar, Ahmad Sabirin; Yaacob, Ahmad Akmalhakim; Zolkapli, Maizatul; Zakaria, Azlan; Abdul Wahab, Mohd Zahrin (UiTM Press, 2010)
This technical paper investigates the effect of doping techniques, type of dopant species and the plate size on the capacitance density of a silicon based capacitor. The substrate of the silicon wafers are highly doped using either solid source (SS) or spin-on dopant (SOD) method. Experiments are carried out at three different diffusion temperatures, 900oC, 1000oC and 1050oC. Results show that the diffusion by spin-on dopant gives a higher capacitance density compared to diffusion by solid source while larger plate size leads to a larger capacitance value. In addition, the experiment also shows that n-type wafer heavily doped with phosphorus exhibits a higher capacitance density.